Artistic casting of complex 3D printed objects with PLA as an alternative to the wax model - Díaz-Alemán, Manuel Drago; Meier, Cecile; Pérez-Conesa, Itahisa; Saorín, J. Luis (Arte, Individuo y Sociedad, 2019)
This paper addresses strategies that allow the introduction of computer-designed models as substitutes for the wax models used traditionally in artistic casting. These digital models are manufactured by 3D printing in polylactic acid (PLA), material that due to its properties is a viable substitute to wax, within the processes of artistic casting using Ceramic Shell Casting. To check the viability there have been designed two complex models that are difficult to achieve with traditional techniques. In particular, a hollow figurative bust and a figurative synthesis of plant forms with a gradient structural solution. In addition, a study was made with different techniques to unify the texture of layers presented by the objects manufactured by 3D printing. It is proven that it is feasible to introduce PLA models in the smelting process at lower cost and less time than with traditional techniques. In addition you can melt metal shapes that are not possible to create with manual techniques.
Keywords: PLA; artistic casting; 3D printing; wax; sculpture